The Effect of Using Pictures on Students’ Speaking Ability at Grade Eight of SMPN 2 Seputih Mataram Lampung Tengah - Laurisa Widyaningrum (International Conference on Education and Language (ICEL), 2014)
This is an experimental research that was aimed to find out the effect of using pictures on students’ speaking ability at grade eight of SMPN 2 SeputihMataram Lampung Tengah 2014. Speaking is defined as an oral expression that involves not only to the use of right patterns of rhythm and intonation but also to the right order to convey the right meaning. Pictures were applied to increase the students’ speaking ability which was low. They were used as one of visual aids to help and to guide the students to speak and make them interested in learning English. Data were collected by incorporating two pre-tests and two post-tests in experimental group and control group. In the experimental group, the researcher gave treatment by using pictures.  While in the control group received traditional teaching. Data analysis was attempted using t-Test for two group design. The result indicated that p-value 1% = 2.65, 5% = 2.00, and t-value = 10.59. It means p-value is smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The researcher concluded that the use of pictures was more effective than traditional teaching in improving students’ speaking ability. These findings suggest that there is effect of using pictures on the students’ speaking ability at grade eight of SMP N 2 SeputihMataramlampung Tengah. It is suggested that the teacher uses pictures for teaching speaking.